Unconventional, alternative and complementary therapies in oncology: hope or curse? - J. Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2004)
Unconventional therapies, Complementary/Alternative Medicine (CAM), are becoming more and more popular among cancer patients. The phenomenon is based on an easy access to the world wide web and to the increasing consciousness and determination of patients and their families. CAM approaches can modulate both the efficacy of the standard treatment and its adverse effects. Complementary treatment applied along with a classical therapy e. g. proper diet, acupuncture, yoga, meditation or some herbs can significantly improve patients’ quality of life and their determination to fight cancer. However, patients treated solely with CAM as an alternative to the standard treatment have dramatically poorer prognoses. Moreover, several alternative approaches, mostly herbal drugs may induce life-threatening side effects such as a liver or kidney failure. In 1992, the National Institutes of Health created the Office of Alternative Medicine which has been collecting information on every aspect of unconventional therapies. One assumes that around 99% of cancer patients have heard of CAM and of those, 83.3% have used at least one CAM approach. More than 30% of CAM-treated patients believe that they can be totally cured. The CAM is mostly used in the case of an advanced cancer, and such patients are more optimistic and have more control over their own situation. Moreover, patients receiving CAM treatment feel abandoned by their doctors and are not satisfied with outcomes of the standard treatment. Oncologists must be aware that unconventional treatments are popular among the society and that they also have to discuss this aspect of therapy with their patients. As a result of such a discussion the patient will be convinced of a good and complete treatment applied by his doctor, and the doctor will have a total control over the whole therapy.